ASPEK-ASPEK RASIO KEUANGAN BANK UNTUK MENILAI KINERJA KEUANGAN BANK Penelitian pada Bank BUMN yang Tercatat di BEI) - N P, Maria Goretti Wi Endang (Profit: Jurnal Adminsitrasi Bisnis, 2008)
Abstract This research wants to analyze level of State Owned Banking (Bank Mandiri, BRI and BNI) liquidity and profitability in 2006 to 2007. The result of research showed that liquidity among those banks is good. It is proved by persentation of quick ratio and bank ratio from those are greater than GWM compulsory that required by Bank Indonesia by 12%. Furthermore, profitability of those banks seen from rate return on loans and interest margin on loans is good. Since, ratio of those is larger than 9.50% (standard of BI). It means that flows of credit has been running effective and increase the return of loans. Keywords: financial asset, liquidity and profitability, rate return on loans and interest margin on loans, quick ratio and bank ratio